Analysis of Marketing Strategies in the context of Green Products - Jaggi, Pallavi; Rini, (Gyan Management Journal, 2023)
Purpose - In the context of the consumer durables products business,  transformational marketing tactics have been made possible by  the implementation of holistic marketing in the era of Industrial  Revolution 4.0. As a result of customers’ active involvement with  marketers, the range of marketing methods has expanded in line  with consumer knowledge of climate sensitivity, establishing the  groundwork for environmentally friendly products. Green marketing  makes it possible for businesses to create and sell environmentally  friendly goods. Enhancing the company’s reputation, making it  simple to reach a specific consumer group (Niche marketing), and  most crucially, retaining its competitive edge. As consumers become  increasingly conscious of the quality of the items, green products are  intriguing topics to debate. Consumer education about product quality  strives to promote environmental protection and health advantages.  The decision of consumers to purchase green products is influenced by  a variety of factors. In the context of green products in the consumer  durables business, the current study emphasizes the fundamentals  of marketing strategies and related techniques. Consumer durables  encompass anything from FMCG to electronic devices (white and  brown products).
Keywords: Green product; eco-friendly good; environment friendly durables; energy efficient green products; green marketing strategies; and antecedents of green marketing strategies